Health Impacts of E-Cigarettes: A Comprehensive Review of the Evidence and Public Health Implications - Bieniak-Pentchev, Magdalena; Kotowicz, Michał; Koczkodaj, Maria (Quality in Sport, 2025)
Electronic cigarettes, also known as e-cigarettes or Electronic Nicotine Delivery Systems (ENDS), have quickly become a well-liked substitute for conventional tobacco products, especially among teenagers and young people. Despite being marketed as a smoking cessation assistance and harm reduction tool, their safety profile is still being investigated. The health implications of e-cigarette use on the respiratory, cardiovascular, and neurological systems, as well as possible carcinogenic consequences, are examined in this thorough literature analysis. Airway inflammation, elevated cardiovascular risk markers, mental health comorbidities, and biomarkers of DNA damage are only a few of the detrimental health impacts that are now supported by data. The long-term safety of vaping is still unknown, despite some research suggesting lower exposure to dangerous chemicals as compared to combustible tobacco. The necessity of balanced public health measures is emphasized, and global regulatory approaches are also covered. This review concludes by highlighting the significance of prudent regulation and ongoing research to inform clinical and policy decisions on the use of e-cigarettes.